(untitled) (Docentes 2.0 Journal, 2023)
The return to the new normality brought with it a series of changes in the ways of transmitting knowledge, the lack of access to laboratories to carry out practices was one of the main problems of classes in the hybrid modality; therefore, this objective of the research was to implement the use of computer simulators which can remedy the need for quality laboratory practices to achieve significant learning. The research was based on the inductive method, a positivist paradigm with a quantitative approach of experimental design of correlational type and with a cross-section. The selected sample consisted of 17 students with an engineering career in computer and communication technologies of the Autonomous University of Carmen’s information sciences faculty. The methodology used was the application of an instrument in which students’ relationship with technological tools facilitates their learning. The results demonstrated a close relationship with simulators, and their implementation generated better results, decreasing course failure; it was required to continue generating this type of course design, including real-time access technologies to build their knowledge; the research demonstrated the use of simulators has an impact on learning.